CGIAR Systemwide Program on Participatory Research and Gender Analysis - Gómez, Juliana (International Center for Tropical Agriculture, 2009)
The PRGA is currently implementing its phase III (2008-2012), however, the key factors that underpinned the Program’s work at the beginning of Phase II (2003–2007) still apply today: §A majority of agricultural research systems, including in the CG System, still lack a critical mass of participatory-research and genderanalysis practitioners §There is still little recognition or practice of gender analysis §There is still an unmet demand for capacity development in gender-analysis and participatory-research methods §Learning and change need to be institutionalized, so that participatory research and gender analysis can be mainstreamed in agricultural R&D thinking and practice. The strategic platform for Phase III focuses on three overarching thematic areas: (1) Climate change; (2) Food security, building on the Program’s traditional research areas of plant breeding and natural-resources research; and (3) Supporting actions for gender mainstreaming.